The Identitas Beragama untuk Era Masyarakat 5.0 - Holijah Holijah; Achmad Busiri (Nizham Jurnal Studi Keislaman, 2021)
The era of society 5.0 is an era where humans have a hybrid life. Humans are side by side with technology that has almost the same intelligence as humans, but the difference is that if humans are God's creation, then technology is human creation. The use of artificial intelligence can be fully controlled by humans. So to bring out the controller in this situation, a human religious identity is needed. Religious identity is able to accommodate the factors that influence human development in the era of society 5.0. In society 5.0 there are three dimensions, namely innovative policies, having an entrepreneurial spirit, and having skills in entrepreneurship. These three dimensions, if based on human understanding of religion through their respective identities in their respective religions, will increasingly direct the development of this era to be more advanced.